CULTURAL TERMS TRANSLATION IN HIRATA’S LASKAR PELANGI AND THE IMPACT ON THE TRANSLATION QUALITY - Kuncara, Singgih Daru (Fakultas Ilmu Budaya, Universitas Mulawarman, 2015)
This paper aims to evaluate the translation of cultural terms in English version of of the Hirata’s Laskar Pelangi. This paper investigates also the translation quality of those cultural terms. The data, in this study, are the terms of culture that exist in the novel. The finding of the cultural term is divided into five categories. It consists of ecology, material, social, organization, customs, ideas, motion and habits. Overall, translation cultural terms lead to reduce the level of acceptability and readability of the translation quality.Keywords: translation, cultural terms, laskar pelangi, rainbow troops